VIABILITY STATUS OF DIABETES MELITUS PATIENTS WITH COMPLICATIONS OF HYPERGLYCEMIA, CETOASIDOSIS, AND GANGRENE - Norshinta Anggraini Putri; Hari Basuki Notobroto (Jurnal Berkala Epidemiologi, 2020)
Background: Indonesia ranked the seventh position of the most diabetes patients among other countries. Several risk factors affected the viability of Diabetes Mellitus (DM) patients, such as sex, age, type of DM, obesity, diet program, and family history of DM. Purpose: This research aims to analyze the variables that affect the viability of DM patients with complications. Methods: This research used descriptive analytic research with cross-sectional research design. The population used in this research was DM patients with complications (hyperglycemia, ketoacidosis, and gangrene) who were hospitalized at X Hospital in Madiun, which recorded in January-December 2018. This research used a total sample with data obtainment techniques used medical records data sources of DM patients with complications (hyperglycemia, ketoacidosis, and gangrene) which recorded in January-December 2018 and observed until January 2019. The analysis technique used was survival analysis using kaplan meier, breslow, and cox regression. Results: The characteristics of respondents were the majority were 60 years old and over (53.70%) and were female respondents (63%). Based on the research results of several variables, only diet program variable which was significant among all independent variables (p = 0.01; HR = 3.74; 95% CI = 1.65 <OR <8.48), which suspected to affect the viability of DM patients with complications (hyperglycemia, ketoacidosis, and gangrene). Conclusion: The most influential risk factor is diet program.